Examining three roles of urban "portals" in their relationship with "places" using social media photographs. (July 2019) - Qian, Xiao; Heath, Tim
Abstract: Portals are the transition spaces between paths and places in an urban environment such as the entrance to a square from a connecting street. This paper aims to explore different forms of portals by considering their relationship with places. In doing so, a people-generated image analysis was adopted for two case studies conducted in popular Chinese recreational venues: Sanlitun Village, Beijing; and Xintiandi, Shanghai. Through an analysis of nearly 53, 000 Instagram photographs, three different roles that a portal can fulfil are identified and defined as the 'doorway', the 'showroom', and the 'place'. These typologies are derived from a deeper understanding of urban space through the 'eyes of the users', and this knowledge can in turn influence the design process for the public realm and urban spaces. Graphical abstract: Permissions from joannahiew and chulheepark are shown below (my Instagram ID is joomoly).Unlabelled Image Highlights: Portals are transition spaces providing an interactive preview of adjacent places. There are three types of portals identified: the 'doorway', the 'showroom', and the 'place'. The 'doorway' allows active and passive participation to coexist; it can be connected with any place. The 'showroom' enables passive participators to collect information; it suits the place with a thematic expression. The 'place' encourages people to attend events and build relations with surroundings; it suits the place of participation.